Koncepcja antropologiczna zawarta w rozprawie "Osoba i czyn" Karola Wojtyły jako podstawa refleksji o twórczości artystycznej = Anthropological conception enclosed in "Acting Person", a dissertation by Karol Wojtyla, as a ground for reflections on artistic creativity - Koszewska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The philosophy of the human person that was presented by cardinal Karol Wojtyla in his dissertation "Acting Person" (orig. "soba i czyn", 1969) not only is one of the most weighty conceptions of the twentieth century?s philosophical output, but it also constitutes a philosophical-anthropological foundation for the rest of the autor`s papers, remaining a fundamental idea permeating all his works.
Keywords: Jan Paweł II, papież (1929-2005); antropologia filozoficzna; filozofia człowieka; człowiek; działania ludzi